Modelagem da perda de solos e suas relações com a estrutura fundiária na consolidação do agronegócio no cerrado setentrional - Gamper, Mateus Araujo Bezerra (2023)
The northern portion of the Cerrado Biome is considered the last agricultural frontier in the country, reorganizing the geographic space of the region in recent decades, being the object of sectorial public policies. The transformation of this region led to an increase in the production of agricultural commodities in the region, which implies environmental impacts inherent to large-scale agricultural production, the main one being the erosion of agricultural soils. In this sense, the objective is to evaluate the relationship between the consolidation of the agrarian structure and the spatial and temporal variation of soil loss in the Northern Cerrado for the production of agricultural commodities between 1990 and 2020, considering the role of the periurban area and urban. The proposal has as study area the municipality of São Desidério - BA, the main agricultural producer in the region with the highest agricultural GDP in the country in 2018. To achieve this objective, the mathematical model of the Revised Universal Soil Loss Equation (EUPS) is used. -R / RUSLE) – applied for the years 1990, 1996, 2002, 2008, 2014 and 2020, with soil losses calculated for each agricultural property, classified according to the type of rural module (small farms, small , medium and large properties), also considering the legal reserves. The results obtained reveal a distinction in two groups: the constant increase in soil loss in small, medium and large properties and higher losses for smallholdings and legal reserves in all years analyzed. In the first group, the factor that controlled the increase in soil losses was the soil cover (CP), while in the second, the factors that controlled the highest soil losses during the entire period were the slope length (L) and slope (S) and the soil (K). This spatial and temporal structure of soil losses in the municipality indicates that soil loss increased in the largest properties due to the conversion of the Cerrado, despite being in the most suitable reliefs and soils for agriculture and livestock. While in smallholdings and legal reserves, the higher values ​​are due to the natural characteristics of the municipality, as these are, in general, in more sloping reliefs and soils that are more fragile. It is observed, in this sense, that the land structure is a determining factor to explain the loss of soil in the municipality.